Aerobic fitness in youth with chronic disease and mobility impairments: assessment and treatment - Davoli, Gabriela Barroso de Queiroz (2023)
Introduction: Primary or secondary changes in the skeletal muscle system are observed in most childhood chronic diseases, which in this thesis included spina bifida (SB), spinal muscular atrophy (SMA), Charcot-Marie-Tooth disease (CMT), Duchenne and Becker muscular dystrophy (DMD e BMD), congenital muscular dystrophy (CMD), and myotonic dystrophy type 1 (MD1). These changes mainly affect the patient\'s lower limbs impairing their mobility. It increases the risk of a sedentary lifestyle and deconditioning, creating a \"vicious cycle\" of activity discouragement and worsening overall conditioning. Obesity and cardiovascular disease are additional inactivity problems, and aerobic fitness is reported as the main associated factor. Nevertheless, limited evidence is available about assessing and improving aerobic fitness in youth with chronic disease. Aim: to explore and create insight for alternative tests to assess the aerobic fitness of youth with chronic diseases which are non-ambulatory or have a mobility impairment and to test the effects of an upper-limb combined program on this group\'s aerobic fitness and muscle strength. Methods: In chapter two, three different cardiopulmonary exercise tests (CPET) were used: the arm-crank CPET, the 10 meters shuttle ride test (10m-SRT), and the short-time continuous push-test (ST-CPT) to test the validity and reliability of the ST-CPT for wheelchair-users patients with SB, and to develop a prediction model of absolute oxygen uptake (VO2peak) for this test. In chapter three, a systematic review of literature following the PRISMA guidelines was performed to synthesize evidence about the quality and feasibility of CPET in NMDs and patients\' aerobic fitness. One independent reviewer searched pubMed/MEDLINE, EMBASE, SCOPUS, and Web of Science databases between September and October 2020. At chapter four, two CPETs were used: the armcrank CPET and the anti-gravity treadmill CPET to assess the quality and feasibility of these CPETs in mobility-impaired patients with SMA and BMD and to compare the exercise responses of the patients in the two tests. In chapter five, non-ambulatory and mobility-impaired patients with SB, CMT, CMD, and MD1 were randomized and submitted to a 14-week upper limb combined program consisting of a high-intensityinterval training - HIIT (8 weeks) and strength training (6 weeks) twice a week. Results: Chapter two shows that the ST-CPT is a valid and reliable maximal field test to assess aerobic fitness in wheelchair-users patients with SB. The distance covered in this test and the patient\'s body mass may estimate 72% of the patient\'s absolute VO2 peak. Chapter three presents that CPET is feasible for ambulatory patients with NMDs when their functional level and exercise modality are considered. However, there is still a vast potential for standardizing and designing disease-specific CPET protocols for patients with NMDs. Chapter four indicates that the anti-gravity treadmill CPET is a feasible and accepted test to assess the aerobic fitness of SMA and BMD patients. Conversely, the arm-crank CPET needs some adaptations to be feasible for this group. Chapter five shows that the upper limbs 14-week combined program improves aerobic fitness, performance, and flexor muscle strength of youth with SB, CMT, CMD, and MD1. Conclusion: This thesis brought a new perspective on pediatric rehabilitation regarding aerobic fitness assessment and treatment for chronic childhood diseases. Nevertheless, there are still many unanswered questions to be responded by future studies.